Corrosion mechanism and fatigue behavior of 2A70-T6 aluminum alloy under alternating corrosion and fatigue. Issue 5 (2nd September 2021) - Fu, Lei; Li, Hui; Lin, Li; Wang, Qingyuan; Fan, Qi; Huang, Xinjie; Li, XiuLan; Lai, Sheng; Chen, Lifei
Abstract : Purpose: Most supersonic aircraft were manufactured using 2A70 aluminum alloy. The purpose of this paper is to study the corrosion mechanism and fatigue behavior of an aircraft in a semi-industrial atmospheric corrosive environment, alternating effects of corrosion and fatigue were used to simulate the aircraft's ground parking corrosion and air flight fatigue. Design/methodology/approach: For this purpose, the aluminum alloy samples were subjected to pre-corrosion and alternating corrosion-fatigue experiments. The failure mechanisms of corrosion and corrosion fatigue were analyzed using microscopic characterization methods of electrochemical testing, X-ray diffraction and scanning electron microscopy. Miner's linear cumulative damage rule was used to predict the fatigue life of aluminum alloy and to obtain its safe fatigue life. Findings: The results showed that the corrosion damage caused by the corrosive environment was gradually connected by pitting pits to form denudation pits along grain boundaries. The deep excavation of chloride ions and the presence of intergranular copper-rich phases result in severe intergranular corrosion morphology. During cyclic loading, alternating hardening and softening occurred. The stress concentration caused by surface pitting pits and denudation pits initiated fatigue cracks at intergranular corrosion products. At the same time, the initiation of multiple fatigue crack sources was caused by the corrosion environment and the morphology of the transient fracture zone was also changed, but the crack propagation rate was not basically affected. The polarization curve and impedance analysis results showed that the corrosion rate increases first, decreases and then increases. Fatigue failure behavior was directly related to micro characteristics such as corrosion pits and microcracks. Originality/value: In this research, alternating effects of corrosion and fatigue were used to simulate the aircraft's ground parking corrosion and air flight fatigue. To study the corrosion mechanism and fatigue behavior of an aircraft in a semi-industrial atmospheric corrosive environment, the Miner's linear cumulative damage rule was used to predict the fatigue life of aluminum alloy and to obtain its safe fatigue life.